PENGARUH EKSTRAK BIJI PEPAYA (carica papaya L.) DAN EKSTRAK DAUN MIMBA (Azadirachta indica A.Juss) DAN CAMPURAN EKSTRAK BIJI PEPAYA ( carica papaya L.) DAN EKSTRAK DAUN MIMBA (Azadirachta indica A.Juss) TERHADAP DIAMETER TUBULUS SEMINIFERUS, SEL LEYDIG DAN BOBOT TESTIS MENCIT (Mus musculus) - Apolonia M; Sukarjati sukarjati (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2017)
Papaya (Carica papaya L. ) and Neem (Azadirachia indica A.Juss) Tree are planted as an ornamental tree and have a character as a brush plant. They vegetated in tropical and subtropical region. The seed of papaya and Neem leaf are also include of a potential plants as a antifertility. Types of bioactif compounds contained in plants, the main compounds that are derived from the steroids, alkaloids, isoflavanoid, tripernoid, and activity as xanthon antifertilities. This encourages the researcher to know the influence of ethanol seed papaya extract and neem leaf extract towards diameter of seminiferous tubule, leydig cell and the testicular weight mice (Mus musculus). The sample of this research is the mice by as much as 21 tail with a weight of 20-30 grams, aged 2.5 months. Murine in to 3 groups, each group is divided 7 treatment. As for the treatments given are extracts of flowers, leaves, and roots of hibiscus with dose control, 50, and 100 mg/kg. Granting of extracts for 35 days. On day 37 mice are in surgery for testicular weight to observations taken, the volume of the testes. The testes then made preparations and measured diameter of seminiferous tubules. This research is experimental research using Random Complete Group. The data obtained were analyzed with variant analysis (ANOVA) in one direction and continued with test LSD (Least Significant Different). The results of the research there shows the influence of the ethanol papaya seed extract, meem leaf extracy and also the micture of papaya seed extract and neem leaf extract towards the weight of mice, leydig cell and the diameter of seminiferous tubule (P < 0.05). The best result to decrease the testicular weight and diameter of seminiferous tubule was showed by the neem with the weight of 100 mg/kg BB. The best result to decrease the leydig cell was showed on the mixture of papaya seed extract and neem leaf extract in dosage of 100 mg/kg BB. This study showed that papaya seed extract, neem leaf extract and the mixture of papaya seed extract and neem leaf extract able to decrease the testicular weight, diameter of seminiferous and leydig cell. In the next day, this research supposed to be able as an antifertility in male.